Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Find the solution to the system of equations given below using elimination by addition.

15x + 15y = 60
5x - 5y = 40


Sagot :

15x + 15y = 60
5x - 5y = 40

To use elimination by addition, you need to get variables in one equation the same but negative in the other equation. For example, to use addition elimination to match the first equation, the second equation has to be - 15x or -15y. 
Luckily, the second equation is easily manipulated to get to -15y.
To go from -5y to -15y you just need to multiply by 3, so we multiply the whole second equation by 3:

3(5x - 5y = 40)
15x - 15y = 120

Now we can add the two equations to "eliminate" the y's
   
   15x + 15 y = 60
+ 15x - 15y = 120
  30x  + 0y = 180

now solve for x: 

30x = 180
divide both sides by 30
x = 6

Now that we solved for x, we can plug it back into the original equations to get y:
15(6) + 15y = 60
90 + 15y = 60
15y = -30
y = -2

5(6) - 5y = 40
30 - 5y = 40
-5y = 10
y = -2

x = 6 and y = -2
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.